2017
DOI: 10.5194/angeo-35-253-2017
|View full text |Cite
|
Sign up to set email alerts
|

Average plasma sheet polytropic index as observed by THEMIS

Abstract: Abstract. Multi-spacecraft data from the years 2008 to 2015 of the THEMIS mission particularly in the near-Earth plasma sheet are used in order to empirically determine the polytropic index in the quiet and active time magnetotail. The results of a number of previous studies in the 1990s can be confirmed. An analysis of the total database, although showing poor correlation, results in an average polytropic index of γ = 1.72. The active time plasma sheet is well correlated with an average γ = 1.49. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
3
2
0
Order By: Relevance
“…Similar feature in the radial profile of γ at Earth was reported by Frühauff et al (2017), who suggested a connection between γ and the flow-braking region in the near-Earth magnetotail region. Similar feature in the radial profile of γ at Earth was reported by Frühauff et al (2017), who suggested a connection between γ and the flow-braking region in the near-Earth magnetotail region.…”
Section: Summary and Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Similar feature in the radial profile of γ at Earth was reported by Frühauff et al (2017), who suggested a connection between γ and the flow-braking region in the near-Earth magnetotail region. Similar feature in the radial profile of γ at Earth was reported by Frühauff et al (2017), who suggested a connection between γ and the flow-braking region in the near-Earth magnetotail region.…”
Section: Summary and Discussionsupporting
confidence: 86%
“…Analysis of the polytropic index γ with radial distance shows a minimum in γ at R~1.4 R M . Similar feature in the radial profile of γ at Earth was reported by Frühauff et al (2017), who suggested a connection between γ and the flow-braking region in the near-Earth magnetotail region. At Mercury, this minimum also occurs near the region where Poh et al (2017b) reported observations of Mercury's substorm current wedge.…”
Section: Summary and Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Therefore, the polytropic index can be estimated from either the number density‐thermal pressure ( n ‐ p ) relation or the number density‐temperature ( n ‐ T ) relation. Using the linear fit between the logarithms of number density and those of thermal pressure (or temperature), previous studies examined thermodynamic conditions for plasmas in the various regions near the terrestrial magnetosphere, such as the interplanetary space (Kartalev et al, ; Newbury et al, ; Nicolaou et al, ), the magnetosheath (Pang et al, ; Song et al, ), and the plasma sheet (Baumjohann & Paschmann, ; Frühauff et al, ; Huang et al, ; Pang et al, ; Zhu, ).…”
Section: Introductionmentioning
confidence: 99%